2018
DOI: 10.1038/s41598-018-26732-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nanobody-based lateral flow assay to detect active Trypanosoma congolense infections

Abstract: Animal African trypanosomosis (AAT), a disease affecting livestock, is caused by parasites of the Trypanosoma genus (mainly T. vivax and T. congolense). AAT is widespread in Sub-Saharan Africa, where it continues to impose a heavy socio-economic burden as it renders development of sustainable livestock rearing very strenuous. Active case-finding and the identification of infected animals prior to initiation of drug treatment requires the availability of sensitive and specific diagnostic tests. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 78 publications
1
54
0
1
Order By: Relevance
“…Here, we present the application of such an “unbiased” approach to the immunization of camelids with the aim of generating Nbs that can be employed for (i) the development of parasite-specific antigen-based immunoassays and (ii) the identification of the target antigen via Nb-mediated immunocapturing followed by MS analysis. Our group has previously adopted this strategy for the identification of novel biomarkers for the detection of active T. congolense infections [ 24 , 39 ]. The immunization of alpacas with soluble proteome and secretome fractions from T. congolense yielded highly specific Nbs targeting the glycolytic enzymes T. congolense aldolase ( Tco ALD) and T. congolense pyruvate kinase ( Tco PYK), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we present the application of such an “unbiased” approach to the immunization of camelids with the aim of generating Nbs that can be employed for (i) the development of parasite-specific antigen-based immunoassays and (ii) the identification of the target antigen via Nb-mediated immunocapturing followed by MS analysis. Our group has previously adopted this strategy for the identification of novel biomarkers for the detection of active T. congolense infections [ 24 , 39 ]. The immunization of alpacas with soluble proteome and secretome fractions from T. congolense yielded highly specific Nbs targeting the glycolytic enzymes T. congolense aldolase ( Tco ALD) and T. congolense pyruvate kinase ( Tco PYK), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The identified Nbs are then used to determine the nature of their target antigens via immunocapturing followed by mass spectrometry (MS). The approach is “unbiased” given that Nb library construction is performed without prior knowledge of the target antigen(s) recognized by the identified binders [ 24 , 39 ]. Here, we report the identification of a single anti- T. evansi secretome Nb (Nb11) after immunizing an alpaca with soluble lysate preparations from different T. evansi strains followed by panning and screening against the T. evansi secretome.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological inhibition or RNAi silencing of this enzyme causes ATP depletion, cell growth arrest, and parasite death ( Albert et al, 2005 , Coustou et al, 2003 , Worku et al, 2015 ). Additionally, the antigenic properties of PK in T. evansi and T. congolense are known ( Pinto Torres et al, 2018 , Yadav et al, 2017 ), and PK has been identified as a diagnostic biomarker in T. congolense ( Pinto Torres et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only way to confirm a diagnosis in infected animals is to demonstrate and identify the parasites in blood and other bodily fluids (which is in itself difficult as parasite numbers are generally low). Most treatment of AAT is therefore presumptive, which has costs for farmers and their perception of the efficacy of treatment [54,55]. The lack of a simple diagnostic test similarly makes it difficult to identity and deal with parasitic reservoirs within livestock populations.…”
Section: Objective Activitiesmentioning
confidence: 99%